KAJIAN EVALUASI DRAINASE KAWASAN JALAN SALAK KOTA MADIUN - Aji, Seno (JURNAL AGRI-TEK, 2015)
The salak road often flooded a while during the rainy season. Drainage on the salak road in the rainy season was less than optimal in accommodating some run off sparking inundation points on the road. The rainfall data used in the planning was daily maximum rainfall data for 10 years observation (2004-2013) obtained from PSAWS Madiun. A calculation and recapitulation analysis frequency of rainfall with a method of distribution logs pearson type III. A drainage debits were calculated was discharge which was stored by the duct secondary I and II to put this in terms of water runoff from all regions actuall. The size of the discharge that may be accommodated by the drainage (Q drainage) was 0,782 m 3 /s the amount of discharge flood maximum was 1,0702 m 3 /s. So that capacity secondary drainage inadequate to accommodate discharge maximum because Qdrainage < Qmaksimum. Key Words: The salak road, the rainy season, flood, drainage.